PRIMARY ALLERGY AND ASTHMA PREVENTION: A REVIEW ARTICLE - Sultana, Andry (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
The prevalence of asthma and other allergic diseases had been increasing over the last few decades in both industrialized and developing countries. It is generally recognized that asthma is disease caused by exposure of genetically predisposed individuals to environmental risk factor. Environmental variables might raise or reduce the likelihood of becoming asthma and allergies. These environmental factors can be managed as primary preventive actions by removing risk factors for asthma and allergies